2012
DOI: 10.1597/11-001
|View full text |Cite
|
Sign up to set email alerts
|

Normative Nasalance Scores for the Malay Language

Abstract: Despite small variations, the overall mean nasalance scores in Malay are consistent with published norms in other languages. Age and sex differences were observed but clinically not relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
1
5
1
1
Order By: Relevance
“…This result may be related to the fact that fundamental frequency of girls and boys are similar until puberty (29) . On the other hand, unlike the results found here, differences between genders have been found for languages spoken in Malaysia, Turkey and Arabia, and, in general, nasalance was shown to be higher in girls (13,20,21) . Taken together, these data suggest that gender differences may be present in some languages but not in others.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result may be related to the fact that fundamental frequency of girls and boys are similar until puberty (29) . On the other hand, unlike the results found here, differences between genders have been found for languages spoken in Malaysia, Turkey and Arabia, and, in general, nasalance was shown to be higher in girls (13,20,21) . Taken together, these data suggest that gender differences may be present in some languages but not in others.…”
Section: Discussioncontrasting
confidence: 99%
“…The use of nasometry in different countries soon has shown that nasalance varies according to the language spoken (9)(10)(11)(12)(13) . Studies with Brazilian Portuguese speakers, including children, have shown that nasalance can also vary according to age, gender or the type of emission (syllables and/or sentences) (14,15) , confirming observations for other languages (13,(16)(17)(18)(19)(20)(21)(22) .…”
Section: Introductionsupporting
confidence: 60%
“…Passage have been used for establishing normative nasalance data for oral, nasal, and oronasal stimuli, respectively [1,3,4]. Similar speech materials consisting of oral, nasal, and oronasal stimuli for other languages including Swedish [24], Flemish [34], Malay [35], Vietnamese [36], and Korean [37] have been developed as well. The ranges of normative nasalance scores for oral, nasal, and oronasal stimuli in different languages have been reported as 6.8 to 34.9, 41.3 to 78.0, and 16.9 to 39.5, respectively [24,25,27,32,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
mentioning
confidence: 99%
“…Similar speech materials consisting of oral, nasal, and oronasal stimuli for other languages including Swedish [24], Flemish [34], Malay [35], Vietnamese [36], and Korean [37] have been developed as well. The ranges of normative nasalance scores for oral, nasal, and oronasal stimuli in different languages have been reported as 6.8 to 34.9, 41.3 to 78.0, and 16.9 to 39.5, respectively [24,25,27,32,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Factors affecting normative nasalance scores include difference in composition of phonemes in different speech materials such as higher nasalance for high vowels (e.g, /i/ and /u/) than low vowels (e.g., /ae/ and /a/), dialect, age, gender, and speech intensity [51][52][53][54][55][56][57][58].…”
mentioning
confidence: 99%
“…; Brunnegǻrd;VanDoor, 2009;Van Lierde et al, 2011;Okalidou et al, 2011;Abou-Elsaad et al, 2012; Samman, 2012;Gerek et al, 2012;Ibrahim;Reilly;Kilpatrick, 2012;Bettens et al, 2013; Browne, 2013;Iqueda et al, 2013;Karakoc et al, 2013;Kim et al, 2013;Thorp;Vimik;Stepp, 2013; El-Kassabi et al, 2014;Park et al, 2014;Tuzuner et al, 2014;Awan et al, 2015;Blanton;Lewis, 2015;Bunton, 2015;D'haeseleer et al, 2015;Cho, 2015; Marino et al, 2015;Kim et al, 2016).…”
unclassified